2019
DOI: 10.1007/s00264-018-4274-3
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical stimulation of bone and cartilage: state of the art and future perspectives

Abstract: Introduction Biophysical stimulation is a non-invasive therapy used in orthopaedic practice to increase and enhance reparative and anabolic activities of tissue. Methods A sistematic web-based search for papers was conducted using the following titles: (1) pulsed electromagnetic field (PEMF), capacitively coupled electrical field (CCEF), low intensity pulsed ultrasound system (LIPUS) and biophysical stimulation; (2) bone cells, bone tissue, fracture, non-union, prosthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 70 publications
(70 reference statements)
1
96
0
6
Order By: Relevance
“…BMP2 treatment and exposure to PEMFs characterized by specific physical parameters are used in clinics to favor bone repair in critical conditions [2][3][4]8,19,21]. Among more than 20 identified BMPs, BMP2 is considered one of the most powerful inducing osteogenesis and since 2002 it has been approved for clinical use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMP2 treatment and exposure to PEMFs characterized by specific physical parameters are used in clinics to favor bone repair in critical conditions [2][3][4]8,19,21]. Among more than 20 identified BMPs, BMP2 is considered one of the most powerful inducing osteogenesis and since 2002 it has been approved for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Generally bone fractures heal by standard clinical practices, although approximately 10% patients suffer from delayed unions or non-unions [1]. Electromagnetic field (EMF) exposure represents a safe and efficient non-surgical treatment in promoting bone ununited fracture healing in clinics [2][3][4]. The use of biophysical stimulation in clinical setting is supported by excellent results of in vivo and in vitro studies, which identified the EMF effects on the cells involved in bone repair processes, especially osteoblasts and mesenchymal stem cells (MSCs) [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of bone's bioelectric properties, electrical stimulation for bone regeneration was attempted as early as in the 1950s with Yasuda [22] as the "pioneer" in the field of bone bioelectricity and stimulation. Since then, accelerated bone regeneration due to electrical stimulation has been widely investigated in numerous in vitro, in vivo, in silico, and clinical studies [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Терапевтичний ефект низько-інтенсивних пульсуючих ультразвукових коливань полягає у мікромеханічному пошкодженні ділянки кісткового дефекту звуковою хвилею, що, у свою чергу, спричиняє низку змін на молекулярному та клітинному рівнях, які забезпечують процес загоєння [3,4]. Цей метод здебільшого застосовується при лікуванні переломів трубчастих кісток (зокрема у курців), а також показаний пацієнтам, яким було проведено остеотомію [5][6][7].…”
Section: огляд та обговорення низько-інтенсивні пульсуючі ультразвукоunclassified